Oxidation of 1,2,3 –Propanatriol with Molecular Oxygen Using Pd/Γ-Al2o3 Catalyst in Water Solvent - Henny Theresia V (Institute of Computer Science (IOCS), 2022)
1,2,3-Propanetriol has been oxidized with molecular oxygen and catalysed by heterogeneous catalyst Pd/γ-Al2O3 in water solvent to produce glyceric acid ( 32,62%w ). Glyceric acid was formed then reacted with sodium hydroxide in methanol to produce sodium glycerate ( 27% ). Product of reaction were characterized by FT-IR and 1H-NMR spectroscopy.